Prophenoloxidase-positive tubes derived from the hindguts may be the doorkeeper to detoxify the waste metabolites collected by Malpighian tubules in Lepidoptera insects. (June 2022) - Tang, Yingyu; Zhang, Ying; Zhang, Qiaoli; Chen, Rongbing; Gong, Liyuan; Wei, Xuefei; Yang, Jingfeng; Wu, Kai; Huang, Wuren; Li, Shirong; Toufeeq, Shahzad; Liu, Qiuning; et al.
Abstract: Prophenoloxidase (PPO), an important immunity protein in insects, is mainly produced by hemocytes and released into the hemolymph upon cell lysis. In addition, PPO can also be produced by epidermal cells in the foregut to detoxify the toxic plant secondary metabolites and in the hindgut to kill pathogens through PPO-induced melanization. Previously, we noticed a pair of tubes extended from the larval hindgut became melanized upon staining in dopamine dissolved in 30% ethanol. However, the structure and function of these tubes are largely unknown. In this study, we performed staining of the tubes and the neighboring Malpighian tubule for further confirmation. Eventually, we detected PPO inside epidermal cells of the tubes, and called them as PPO-positive tubes. We observed that the PPO-positive tubes are physically derived from the hindgut but strongly adhere to the Malpighian tubule. Inside the PPO-positive tubes, there is an acellular peritrophic membrane to protect the epidermal cells. Furthermore, the PPO-positive tubes act like a doorkeeper to firstly detoxify the metabolite wastes collected by the Malpighian tubule from the hemolymph. Highlights: Tube-like tissues derived from hindgut in Bombyx mori. The two Tubes can produce prophenoloxidase. The two Tubes may function as the doorkeeper to detoxify some toxic metabolites.